PERAN KOMITMEN ORGANISASIONAL DALAM MEMEDIASI PENGARUH KOMPETENSI, PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PERAWAT - Intan Cahya Kurniasari; Armanu Thoyib; Rofiaty Rofiaty (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. Research aim to analyze influence of 1) Competencies on Organtizational Commitment. 2) Training on Organtizational Commitment. 3) Organization Culture on Organtizational Commitmen. 4) Competencies on Nurses’ Performance. 5) Training on Nurses’ Performance. 6) Organization Culture on Nurses’ Performance. 7) Organizational Commitment on Nurses’ Performance. 8) Role mediation of Organizational Commitmen within the influence of Competencies on Nurses’ Performance. 9) Role mediation of Organizational Commitmen within the influence of Training on Nurses’ Performance. 10) Role mediation of Organizational Commitmen within the influence of Organizational Culture on Nurses Performance. Sample has taken by survey methode by used saturated sampling which mean make all population member as a sample. Research sample were 143 nurses who work at Waluyo Jati Kraksaan Probolinggo Hospital with more than 1 year working time. The analyse tool is Partial Least Square (PLS). The research result competencies, training and organization culture influence organizational commitment directly but didnt have influence on nurses performance. Organizational commitmen have the role mediation fully (complete) by competencies, training with culture to nurses’performance in Waluyo Jati Kraksaan Hospital.